Comparative Study of Students’ Translation Quality Using Printed Dictionary and Post-Editing on Machine Translation Tools from English-Indonesian - Wibowo, Maharya Agung; Oktavia, Witri (Universitas Negeri Padang, 2024)
This research aims to compare the translation quality produced by students using printed dictionary and post-editing on machine translation tools. Participants in this research were students from K7-22 class who have taken Introduction to Translation Class from English Education at Universitas Negeri Padang, totaling 27 students. This research was conducted by using descriptive quantitative research and using translation test as the instrument. Researcher gave two different texts with the same level. When using a printed dictionary, students showed good level of translation quality, with a score of 2.20. Also, when using post-editing on machine translation tools it produces a higher score of 2.65, which shows that the level of translation quality is very good. It can be concluded that comparing the quality of student translations from the two versions that post-editing on machine translation tools provides better translation quality than printed dictionary. However, in each element, printed dictionary and post-editing on machine translation tools show that the accuracy is same. These two translation versions only help students in terms of acceptability and readability. For accuracy, students need to be improved a lot when translating text because there are still shortcomings when using printed dictionary and post-editing on machine translation tools.